Redox- and metal-directed structural diversification in designed metalloprotein assemblies. Issue 49 (1st June 2022) - Kakkis, Albert; Golub, Eyal; Choi, Tae Su; Tezcan, F. Akif
Abstract : Herein we describe a designed protein building block whose self-assembly behaviour is dually gated by the redox state of disulphide bonds and the identity of exogenous metal ions. Abstract : Herein we describe a designed protein building block whose self-assembly behaviour is dually gated by the redox state of disulphide bonds and the identity of exogenous metal ions. This protein construct is shown – through extensive structural and biophysical characterization – to access five distinct oligomeric states, exemplifying how the complex interplay between hydrophobic, metal–ligand, and reversible covalent interactions could be harnessed to obtain multiple, responsive protein architectures from a single building block.